“No Direction Home”: The Life and Literature of Bob Dylan–From “Desolation Row” to the Nobel Prize - Gearon, Liam (Text Matters: A Journal of Literature, Theory and Culture, 2020)
Using the Nobel Prize as a prism through which to view the life and literature of a difficult-to-define artist, this article argues that Dylan’s output is one in which life and literature become, and have always been, indistinguishable. It is the life which has made the literature, through years lived in a particular niche of 1960s counter-cultural history; the lyrics gave voice to a man who was never at ease in the formalities of interview. For a supposed spokesman of a generation Dylan spoke very little except through his songs. So too in the more difficult-to-define later decades, little of his life was spoken of except through song, and some samplings of autobiography. Detailing the historically distinctive features of the Nobel Prize, the article shows how Bob Dylan has, through life and literature, broken down the boundaries between the literary and the popular. The article’s title is drawn, of course, from a famous line in Bob Dylan’s era-defining “Like a Rolling Stone,” one which Martin Scorsese used to title a full-length documentary on the life of Bob Dylan. Dylan here occupies the borderlands where art imitates life, and life imitates art. I argue, contrary to critical consensus, that there is a direction home. In Dylan’s lifetime of existentially staring death (political death, the death of romance) in the face, there is some glimpse of home. It is that glimpse which gives the poet’s lyrical output its endurance as literature.